2021
DOI: 10.1016/j.chest.2021.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Therapy in Sleep-Disordered Breathing

Abstract: Sleep-disordered breathing (SDB) is highly prevalent in adults and leads to significant cardiovascular and neurologic sequelae. Intermittent hypoxia during sleep is a direct consequence of SDB. Administration of nocturnal supplemental oxygen (NSO) has been used as a therapeutic alternative to positive airway pressure (PAP) in SDB. NSO significantly improves oxygen saturation in OSA but is inferior to PAP in terms of reducing apnea severity and may prolong the duration of obstructive apneas. The effect of NSO o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 101 publications
0
14
0
3
Order By: Relevance
“…This is suggested by the study of Kostikas and co-workers who observed that the appropriate CPAP pressure required for elderly patients is, on average, 2.5 mmHg less than that used for younger people adjusted by OSA severity [23,24]. Indeed COT is not a therapeutic option for patients with OSA, as it may prolong the duration of apneas although improving oxygenation [25,26]. The use of COT in COPD with nocturnal desaturation, established many years ago by the NOTT group, has been more recently disputed, while no data are currently available for patients with overlap syndrome [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…This is suggested by the study of Kostikas and co-workers who observed that the appropriate CPAP pressure required for elderly patients is, on average, 2.5 mmHg less than that used for younger people adjusted by OSA severity [23,24]. Indeed COT is not a therapeutic option for patients with OSA, as it may prolong the duration of apneas although improving oxygenation [25,26]. The use of COT in COPD with nocturnal desaturation, established many years ago by the NOTT group, has been more recently disputed, while no data are currently available for patients with overlap syndrome [25,27].…”
Section: Discussionmentioning
confidence: 99%
“…As is well known, hypoxia diminished physiological functions and the overall quality of life. Previous studies have shown continuous positive airway pressure (CPAP) may help to improve HR-QoL, especially physical performance [24,25]. However, CPAP therapy for patients with partial laryngectomy was not adequate.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen therapy has been used as an alternative to CPAP to treat OSA, and despite reducing hypoxemia, it is inferior to CPAP in both reducing AHI and improving most clinical outcomes ( Zeineddine et al, 2021 ). The degree to which non-titrated oxygen can prevent apnea/hypopnea-associated desaturations likely depends on factors such as the duration of pretreatment, the degree of airway closure during an event, and the duration of the event.…”
Section: Discussionmentioning
confidence: 99%